A case of isolated cortical venous thrombosis presenting radiographically as a subacute multifocal leukoencephalopathy, and review of literature. Issue 10 (25th October 2019) - Palmer, Charles Francis; Khalighinejad, Farnaz; Jun-O'Conell, Adalia; Ionete, Carolina
Abstract : A 55-year-old man presented with brief seizure with associated acute aphasia, right head turn and subsequent generalised convulsion. On imaging, he was found to have patchy juxtacortical and cortical T2 hyperintensity with high radiographic suspicion for subacute multifocal leukoencephalopathy. Serum and cerebrospinal fluid testing were unremarkable. Clinically, the patient recovered completely and had no recurrence of symptoms. On follow-up MRI 1 month later, the T2 hyperintensity had resolved almost entirely while hypointensity on susceptibility-weighted angiography MRI remained, suggesting isolated cortical venous thrombosis.